Okay, here we have this:
Considering the provided figure, we are going to find the missing sides, so we obtain the following:
Then according to the altitude rule we obtain the following equality:
(1/3)/x = x/(1/6)
Let's solve for x:
x^2=(1/3)(1/6)
x^2=1/18
x=√(1/18)
x=1/√18
x=1/(3√2)
x=√2/6
Now let's find the other two missing sides using the Pythagorean theorem:
![\begin{gathered} z=\sqrt{\left((1)/(3)\right)^2+\left((√(2))/(6)\right)^2}^ \\ z=√(\lparen1/9)+\left(2/36\right)) \\ z=√(\left(1/9\right)+\left(1/18\right)) \\ z=√(\left(2/18\right)+\left(1/18\right)) \\ z=√(3/18) \\ z=√(1/6) \\ z=1/√(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8s1o1detgx7atogccpxny0n3cwsi8a7leq.png)
Finally let's find y:
![\begin{gathered} y=\sqrt{\left(1/6\right)^2+\left(√(2)/6\right)^2} \\ y=√(\left(1/36\right)+\left(2/36\right)) \\ y=√(3/36) \\ y=√(1/12) \\ y=1/√(12) \\ y=1/\left(2√(3)\right) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4idpyfx9rfomhf96n65k4m6byzi9al5vhn.png)